Effects of decision aids on breast reconstruction: A systematic review and meta‐analysis of randomised controlled trials. Issue 7 (22nd April 2022) - Yang, Shu; Yu, Lin; Zhang, Chunmiao; Xu, Mengmeng; Tian, Qi; Cui, Xuan; Liu, Yantong; Yu, Shuanghan; Cao, Minglu; Zhang, Wei
Abstract: Aims and Objectives: To systematically evaluate the effects of decision aids for women facing breast reconstruction decision on decision conflict, decision regret, knowledge, satisfaction, anxiety and depression. Background: Breast reconstruction decision is not good or bad and should be guided by clinical evidence and patient preferences. Decision aids can increase the patient's decision‐making enthusiasm and ability, improve the quality of decision and promote shared decision‐making between patients and medical staff. Design: Systematic review and meta‐analysis. Methods: Eight databases were conducted from the establishment of the database until October 2021. The PRISMA checklist was selected for analysis in this paper. The meta‐analysis was conducted in Review Manager 5.3. The quality of the studies was assessed using the Cochrane risk‐of‐bias tool. The result is decision conflict, decision regret, knowledge and other secondary outcomes. Sensitivity analysis and subgroup analysis were also conducted. Results: A total of twelve randomised controlled trials (RCTs) were included in the systematic review and meta‐analysis. Meta‐analysis revealed that decision aids could significantly reduce decision conflict and decision regret, improve knowledge, satisfaction and depression and had no influence on anxiety. Conclusions: The results of the systematic review and meta‐analysis reviewed the positive effect of decision aids on the decision‐making of women facing postmastectomy breast reconstruction. In the future, more well‐designed RCTs are needed to confirm the effects of decision aids on the decision‐making of breast reconstruction and nurses should be encouraged to take part in the development of decision aids in accordance with strict standards and apply them to breast cancer patients considering postmastectomy breast reconstruction. Relevance to clinical practice: Our study provides evidence for the effectiveness of decision aids on breast reconstruction and points to the important role of healthcare providers in the use of decision aids and in facilitating shared decision‐making.